Dominance of Methanosarcinales phylotypes and depth-wise distribution of methanogenic community in fresh water sediments of Sitka stream from Czech Republic - Chaudhary, Prem Prashant; Wright, André-Denis G; Brablcová, Lenka; Buriánková, Iva; Bednařík, Adam; Rulík, Martin (Current microbiology, 2014)
The variation in the diversity of methanogens in sediment depths from Sitka stream was studied by constructing a 16S rRNA gene library using methanogen-specific primers and a denaturing gradient gel electrophoresis (DGGE)-based approach. A total of nine different phylotypes from the 16S rRNA library were obtained, and all of them were clustered within the order Methanosarcinales. These nine phylotypes likely represent nine new species and at least 5-6 new genera. Similarly, DGGE analysis revealed an increase in the diversity of methanogens with an increase in sediment depth. These results suggest that Methanosarcinales phylotypes might be the dominant methanogens in the sediment from Sitka stream, and the diversity of methanogens increases as the depth increases. Results of the present study will help in making effective strategies to monitor the dominant methanogen phylotypes and methane emissions in the environment.
Keywords: Denaturing Gradient Gel Electrophoresis; Cluster Analysis; geologické sedimenty; Methanosarcinales; fylogeneze; DNA archebakterií; RNA, Ribosomal, 16S; Česká republika; Sequence Analysis, DNA; Phylogeny; řeky; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; shluková analýza; společenstvo; Rivers; DNA, Archaeal; Czech Republic; Geologic Sediments; denaturační gradientová gelová elektroforéza; Biota; RNA ribozomální 16S; Molecular Sequence Data; DNA, Ribosomal